Based on T-spherical fuzzy environment: a combination of FWZIC and FDOSM for prioritising COVID-19 vaccine dose recipients - Al-Amoodi, Abdullah Hussein Abdullah (Tanjong Malim, 2021)
Based on T-spherical fuzzy environment: a combination of FWZIC and FDOSM for prioritising COVID-19 vaccine dose recipients by Al-Amoodi, Abdullah Hussein Abdullah